Composition of a Research Paper - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2022)
A research paper is a verbal presentation of research finding in reliable and persuasive manner. A researcher has a problem/question or questions on particular subject, area or issue. A research finds the answer to this question. The answer of this question is the finding of the research. A thesis statement is a sentence that includes the finding of the research, the main point of the research paper. The paper clearly states the main point and supports it with reasoning, data, examples and interpretations. The topic of the research paper includes the research area and the perspective of the researcher on it. In other words, it attempts to provide a glimpse of the main point as far as possible. The topic is linked to thesis statement. The thesis statement is clarified and a bit more elaborated in abstract. "Keywords" in research paper lists some words that are closely related to the main point of the paper. Introduction briefly presents the background of the research area and perspective (theory). Literature review surveys earlier researches and finds the research gap. The purpose of the research is to fill this gap. The secondary sources like books and articles are acknowledged and cited in the text and listed in the references. Introduction and literature review are based on secondary sources but analysis and interpretation has your own voice. We can use the earlier researches and books in our paper but the statement of the paper should be different from earlier works. Others' views should not dominate our paper but our own voice should be leading others with additional emphasis.